Pemanfaatan limbah kotoran kambing menjadi pupuk organik untuk mendukung pertanian berkelanjutan - Fikri Aulia; Wikan Budi Utami; Indira Gayatri Dian Pramesti; Febrian Rizalul Amin; Ilva Vidiana (Universitas Pendidikan Indonesia, 2026)
Reliance on chemical fertilizers in Petungsewu Village, Wagir District, has led to a decline in land quality, threatening the sustainability of local agriculture. On the other hand, the abundant goat manure waste has not been utilized optimally and tends to pollute the environment. This community service activity aims to educate and train the People's Forest Farmers Group (KTHR) in producing organic fertilizers through accelerated fermentation techniques using bioactivators. The methods used are technical assistance and direct practice of fertilizer manufacturing with control of moisture and aeration parameters. The results of the activity showed that within three weeks, goat manure waste was successfully transformed into mature organic fertilizer with physical characteristics of being crumbly, dark in color, and free of an ammonia odor. Application tests on cayenne pepper plants, the leading commodity in the Wagir region, showed a more stable increase in vegetative growth than with conventional chemical fertilizers. In addition to improving soil chemistry, this initiative has a positive economic impact by reducing farmers' production costs. Overall, this independent waste treatment is a sure strategy in supporting sustainable agriculture and fertilizer independence at the village level.